Inhibition of angiotensin II-induced cardiac hypertrophy and associated ventricular arrhythmias by a p21 activated kinase 1 bioactive peptide. - Rui Wang; Yanwen Wang; Wee K Lin; Yanmin Zhang; Wei Liu; Kai Huang; Derek A Terrar; R John Solaro; Xin Wang; Yunbo Ke; Ming Lei (PLoS ONE)
Cardiac hypertrophy increases the risk of morbidity and mortality of cardiovascular disease and thus inhibiting such hypertrophy is beneficial. In the present study, we explored the effect of a bioactive peptide (PAP) on angiotensin II (Ang II)-induced hypertrophy and associated ventricular arrhythmias in in vitro and in vivo models. PAP enhances p21 activated kinase 1 (Pak1) activity by increasing the level of phosphorylated Pak1 in cultured neonatal rat ventricular myocytes (NRVMs). Such PAP-induced Pak1 activation is associated with a significant reduction of Ang II-induced hypertrophy in NRVMs and C57BL/6 mice, in vitro and in vivo, respectively. Furthermore, PAP antagonizes ventricular arrhythmias associated with Ang II-induced hypertrophy in mice. Its antiarrhythmic effect is likely to be involved in multiple mechanisms to affect both substrate and trigger of ventricular arrhythmogenesis. Thus our results suggest that Pak1 activation achieved by specific bioactive peptide represents a potential novel therapeutic strategy for cardiac hypertrophy and associated ventricular arrhythmias.